AN ANALYSIS OF THE COMMON PAST TENSE ERRORS COMMITTED IN WRITING BY KURDISH LEARNERS OF EFL - MAJEED, DILVEEN AHMED (Journal of Duhok University, 2023)
Writing is a challenging skill even in the first language, and it is more difficult to write in a foreign language. That is why most of the EFL learners make errors in EFL writing. Error analysis is the method used to identify, classify, explain, and correct errors made by first-year college students in their essays. Errors are significant in three different ways. Firstly, they inform teachers areas that students need more learning. Secondly, they are good evidence for researchers on how language is acquired. Thirdly, they are significant to the learners themselves, because through these error learners can know in which aspects of the language, they lack enough knowledge. This study attempts to analyze past tense errors made by first-year students in order to see what is the most difficult aspect of past tense for the learners. Ten narrative essays composed by Duhok university students were collected and analyzed. Errors made by students were classified into different types and counted in order to see the most frequent error as far as the past tense is considered. Results have shown that the most frequent types of errors were regular verbs in the past, irregular verbs in the past, past perfect tense, past continuous tense, and passive voice in the past. The findings of the study show that past continuous is the most problematic area of the past tense for the participants of this study.